Effects of Different Orthoses on Neuromuscular Activity of Superficial and Deep Shoulder Muscles during Activities of Daily Living and Physiotherapeutic Exercises in Healthy Participants - Grim, Casper; Baumgart, Christian; Schlarmann, Manuel; Hotfiel, Thilo; Javanmardi, Sasha; Hoffmann, Natalie; Kurz, Eduard; Freiwald, Juergen; Engelhardt, Martin; Hoppe, Matthias W. (Journal of Personalized Medicine, 2022)
Background: This study aimed to investigate the effects of different shoulder orthoses on the neuromuscular activity of superficial and deep shoulder muscles during activities of daily living (ADL) and physiotherapeutic exercises. Methods: Ten participants with healthy shoulders (31 +/- 3 years, 23.1 +/- 3.8 kg/m(2)) were randomized to receive a "shoulder sling", an "abduction pillow" and a "variably adjustable orthosis" on the dominant side. With each orthosis, they completed seven ADL with and four physiotherapeutic exercises without wearing the orthoses. An electromyographic system was used to record the neuromuscular activity of three superficial (trapezius, deltoid, pectoralis major) and two deep shoulder muscles (infraspinatus, supraspinatus) using surface and intramuscular fine-wire electrodes. Results: The neuromuscular activity differs between the orthoses during ADL (p <= 0.045), whereby the "variably adjustable orthosis" mostly showed the highest activation levels associated with the worst subjective wearing comfort rated on a visual analog scale. In addition, differences exist between the physiotherapeutic exercises (p <= 0.006) demonstrating the highest activations of the infra- and supraspinatus muscles for assistive elevation and wipe across a table, middle for pendulum and lowest for continuous passive motion exercises. Conclusions: The neuromuscular activity of superficial and deep shoulder muscles differs between the orthoses during ADL and also between the physiotherapeutic exercises.
CRIS-Team WoS Importer:2023-01-06